2021
DOI: 10.1155/2021/3507426
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision Numerical Simulation on the Cyclic High-Pressure Water Slug Injection in a Low-Permeability Reservoir

Abstract: The paper presents a novel waterflooding technique, coupling cyclic high-pressure water slug injection with an asynchronous injection and production procedure, to address the inefficient development of low-permeability oil reservoir in Shengli Oilfield, a pilot test with 5-spot well pattern. Based on the first-hand data from the pilot test, the reservoir model is established. With an in-depth understanding of the mechanism of the novel waterflooding technique, different simulation schemes are employed to scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Compared with conventional flowgeomechanical coupling models [22], where complex coupling schemes, expensive computational cost, and massive input data, such as rock mechanical data and in situ stress data, get involved, the methodology employed in the study characterizes the dominating mechanism of the physical process while keeping the modeling and computational cost low. The methodology has been applied and validated by previous work to both accurately and efficiently simulate the process [9,[23][24][25][26].…”
Section: Simulation Methodology and Integrated Workflowmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with conventional flowgeomechanical coupling models [22], where complex coupling schemes, expensive computational cost, and massive input data, such as rock mechanical data and in situ stress data, get involved, the methodology employed in the study characterizes the dominating mechanism of the physical process while keeping the modeling and computational cost low. The methodology has been applied and validated by previous work to both accurately and efficiently simulate the process [9,[23][24][25][26].…”
Section: Simulation Methodology and Integrated Workflowmentioning
confidence: 99%
“…The dilation-recompaction model finely depicts the relation between the porosity and reservoir pressure as a piecewise and path-dependent function, illustrated in Figure 2 [9,[27][28][29]. Different value is given to the compressibility according to the range of reservoir pressure.…”
Section: Simulation Methodology and Integrated Workflowmentioning
confidence: 99%
See 1 more Smart Citation
“…According to practices in mines in China and foreign countries, cyclic waterflooding is one of the effective means to improve the exploitation effect of low-permeability oilfields [4], and it is advantages for a small investment, quick effects and simple operation [5][6] . It can relieve the rising rate of the aquifer in the low-permeability reservoir and increase the final waterflooding recovery efficiency to some extent [7] . At present, there are many studies on reasonable working systems of cyclic waterflooding [8][9] , cyclic waterflooding parameter optimization [10] , nonlinear percolation of cyclic waterflooding [11] , and macroscopic yield-increasing mechanism of cyclic waterflooding [12] in China and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reliability of the CWI on EOR has been proved by core flooding experiments, field development and numerical simulations, the EOR performances reported by the researchers vary from 3% to 20%, indicating that diverse frequencies trigger various EOR effects. Moreover, few studies have found a critical frequency for the optimal EOR by CWI from a pore-scale perspective; therefore, the correlation between the frequency of water injection and the EOR is still to be revealed [30,31]. In addition, for operability, the field site generally sets the water injection frequency constant based on the engineering experience, rather than the critical frequency of the optimal EOR at the present residual oil saturation.…”
Section: Introductionmentioning
confidence: 99%